O-008 The Financial Impact of ADAPT for Endovascular Treatment of Acute Ischemic Stroke. (26th July 2014) - Turk, A; Turner, R; Chaudry, M; Spiotta, A
Abstract : Introduction: The use of mechanical thrombectomy for treatment of acute ischemic stroke has significantly advanced over the last 5 years. Little data is available analysing the cost relative to the clinical and angiographic outcomes. The aim of this study is to analyze the cost and efficacy of current stroke therapy. Methods: A retrospective review of the chart and hospital financial database of all ischemic stroke cases from 2009–2013 was performed. Three discreet treatment methodologies evolved during this time: traditional Penumbra System (PS), stent retriever with local aspiration (SRLA) and A Direct Aspiration first Pass Technique (ADAPT). Statistical analysis of clinical and angiographic outcomes and costs for each group was performed. Results: 222 patients (45% male) underwent mechanical thrombectomy, with 88% of strokes present in the anterior circulation. PS was used 58%, SRLA 13% and ADAPT in the remaining 29% of cases. PS was able to achieve TICI2b/3 revascularization 79%, SRLA was effective 83% and ADAPT 95% of the time. The average total cost of hospitalization for patients treated with PS was $51, 599, SRLA was $54, 700 and ADAPT $33, 611 (p < 0.0001). The average length of stay was significantly less for ADAPT (7 days) than PS (10.6 days), but not for SLRA (8.3 days) (p = 0.02). Average time to recanalization for PS was 88 min, SRLA was 47 min and ADAPT was 37 min (p < 0.0001). Similar rates of good neurologic outcomes were seen in group PS (36%) as group SRLA (43%) and ADAPT (47%) (p = 0.4). Conclusion: The most cost effective approach to a large intracranial vessel occlusion appears to be direct aspiration with a large bore catheter (without the separator) first and if this fails then proceed with other devices such as a stentriever. Disclosures: A. Turk:1; C; Stryker, Microvention, Penumbra. 2; C; Stryker, Microvention, Covidien, Penumbra, Siemens. 3; C; Stryker, Microvention, Covidien, Siemens, Penumbra. R. Turner: 1; C; Penumbra, Microvention, Stryker. 2; C; Penumbra, Microvention, Stryker. 3; C; Penumbra, Microvention, Stryker. M. Chaudry: 1; C; Penumbra, Microvention, Stryker. 2; C; Penumbra, Microvention, Stryker. 3; C; Penumbra, Microvention, Stryker. A. Spiotta: 1; C; Penumbra, Microvention, Stryker. 2; C; Penumbra, Microvention, Stryker. 3; C; Penumbra, Microvention, Stryker.